Psychological resilience and its relationship with Subjective well-being among Heart patients in Al-Madinah - Al-Madani, Fatima Ramzi; Al-Nuzha, Amjad Hashem (Journal of Educational and Psychological Sciences, 2022)
This study aimed to reveal the relationship between Psychological resilience level and Subjective well-being level among heart patients in Al-Madinah. In this study, the researcher used the descriptive analytical method, that has targeted the frequency of heart patients who visit the heart diseases and surgery center in Al-Madinah. This study was applied on (375) which is a sample of heart patients, who were been chosen by a simple random method. Therefore, in order to achieve the study objectives, the researcher has used the Psychological resilience scale, which is a component of (34) phrases distributed to four dimensions. In addition, the researcher has modified the Subjective well-being scale, which is consisted in its final form of (60) phrases distributed to six dimensions. The study results showed that the Psychological resilience level and the Subjective well-being level of heart patients in Al-Madinah have been within the average level. Moreover, the results of the study indicated that there are no statistically significant differences in the level of Psychological resilience and the level of Subjective well-being of heart patients in Al-Madinah due to the variable of sex. However, the results found that there is a statistically significant (positive) correlation between the level of Psychological resilience and the level of Subjective well-being of heart patients in Al-Madinah at the level of (0.01). The researcher recommends the importance of raising social awareness of heart diseases, its concept, its causes and how to prevent it, and spreading cultural awareness to understand the psychology of heart patients. Also, developing positive attitudes towards themselves in order to accept the disease and having a positive coexistence with the disease.
Keywords: Psychological resilience; Subjective well-being; Heart patients